[Letter from Roy Jasso to Sen. Packwood opposing excise taxes on the behalf of Hispanics] (Tufts Archival Research Center, 2007)
Letter from Roy Jasso, California Hispanic Chamber of Commerce, to Sen. Robert Packwood expressing opposition to his tax reform proposal. Accuses proposal of unfairly disadvantaging small business owners and reminds Packwood that many small business owners are Hispanic. Predicts that tax plan will lead to inflation and single out middle and lower class citizens. Urges Packwood to reconsider the tax plan.